2022
DOI: 10.21315/mjms2022.29.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of American Diabetes Association Diabetes Risk Test: The Malay Version

Abstract: Background: Early detection of high-risk people for type 2 diabetes mellitus (T2DM) using a simple, non-invasive and cost-effective assessment tool helps to identify and prevent members of the community from developing this disease. Therefore, this study aims to translate the American Diabetes Association (ADA) diabetes risk test for Malaysians and then evaluate its validity. Methods: This cross-sectional study was conducted between March 2019 and April 2019. The instrument underwent forward and backward trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Google Forms will be used due to its advantages: easy to build the questionnaire, has unlimited surveys, and is free. ADA diabetes risk test was translated and validated into the Malay language by two experts in the fields of nutrition and dietetics, as well as 35 target users (Nurul Fatihah et al, 2022). The risk score is based on a set of variables not requiring laboratory tests that are used as a tool to predict the risk of T2DM or identify undetected T2DM; these variables are age, gender, and family history of diabetes, history of gestational diabetes in women, history of hypertension, physical activity, and BMI.…”
Section: Recruitmentmentioning
confidence: 99%
“…Google Forms will be used due to its advantages: easy to build the questionnaire, has unlimited surveys, and is free. ADA diabetes risk test was translated and validated into the Malay language by two experts in the fields of nutrition and dietetics, as well as 35 target users (Nurul Fatihah et al, 2022). The risk score is based on a set of variables not requiring laboratory tests that are used as a tool to predict the risk of T2DM or identify undetected T2DM; these variables are age, gender, and family history of diabetes, history of gestational diabetes in women, history of hypertension, physical activity, and BMI.…”
Section: Recruitmentmentioning
confidence: 99%
“…Framingham cardiovascular risk score) derived from the Cox proportional-hazards model. While some studies 64,68,69 have shown that adjustments based on sex or other local factors can significantly improve risk prediction, adjusting such scores for different populations may be difficult, resulting in unaccounted heuristics or biases 70 . In this work, we present a flexible data-driven definition of health risk from a single lab visit.…”
Section: Association Of Lifestyle Factors With Blood Test Reference I...mentioning
confidence: 99%